The Enhancement of Mathematical Problem-Solving Skills among Junior High School Students Using Problem-based Learning - Patunah, Siti; Herman, Tatang; Hasanah, Aan (Jurnal Pendidikan MIPA, 2024)
Improving problem-solving in mathematics education can be achieved by applying a Problem-Based Learning (PBL) approach that prioritizes active student involvement. This research offers a PBL model that is integrated with digital technology to improve students' problem-solving skills more effectively and efficiently. This study aims to analyze the effectiveness of the implementation of the problem-based learning model in improving the problem-solving ability of junior high school seventh-grade students. The research method used was quasi-experimental with a pretest-posttest design of the control group. The research sample consisted of 66 randomly selected seventh-grade students. The selection of 66 students as a research sample was carried out to ensure adequate representativeness, taking into account the diversity of academic backgrounds and problem-solving skills, so that the results of the study can accurately describe the impact of the implementation of Problem-Based Learning (PBL) on various levels of student ability. The instruments used include problem-solving ability tests berjumlah 5 soal and observation sheets for learning activities. The data analysis technique used was the Mann Whitney to see the difference in improvement from the two groups of research samples. The results showed that students' mathematical problem-solving skills experienced a high improvement (Ngain = 0.813) after learning mathematics using problem-based learning. Furthermore, the implementation of the problem-based learning model significantly improves students' mathematical problem-solving skills. These findings indicate that open-ended problem-based learning is one of the effective alternative interventions in improving students' mathematical problem-solving skills. Therefore, educators in the field of mathematics, such as teachers and lecturers, can use open-ended problem-based learning to improve students' mathematical problem-solving skills.         Keywords: problem-based learning, problem-solving skills. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1067-1079